Visual signaling, chemical cues and camouflage in a stomatopod crustacean - Franklin, Amanda. (2017)
Abstract: During contests over resources, animals may avoid escalating to physical combat by first signaling their fighting ability. Numerous studies have demonstrated that colored patches can be used as agonistic signals. However, there are few studies investigating agonistic color signaling in aquatic invertebrates, or in animals with complex visual systems. Stomatopods have the most complex vision known, with up to 20 photoreceptor classes. During territorial contests over refuges, many stomatopod species perform a threat display which exposes a colored patch, the meral spot. Despite several studies predicting that stomatopods assess the meral spot during contests, few have examined this hypothesis. Here, I conduct an in-depth investigation into stomatopod agonistic color signaling using Neogonodactylus oerstedii, a stomatopod found on shallow Caribbean reef and seagrass flats.  Using mathematical visual models, I suggest that the meral spot is a concealable signal; N. oerstedii color morphs provide camouflage from a trichromatic fish predator in seagrass and rubble habitats, but the meral spot is probably detectable by this predator. I also show that meral spot color variation associated with habitat does not function to increase contrast with the local background. Despite this, during territorial contests stomatopods do assess each other's meral spot color. Stomatopods increased their rate of offensive behaviors when competing against a stomatopod with experimentally reduced meral spot UV reflectance. By also manipulating stomatopods' ability to detect chemical cues, I provide evidence that meral spot UV reflectance and chemical cues convey different information to a receiver. In a separate experiment, stomatopods facing an opponent with lightened meral spots increased their rate of coiling behavior (curled position in which the head is above the tail). Further investigation demonstrated that stomatopods with darker meral spots exhibited greater fighting ability, suggesting that meral spots are an honest signal of resource holding potential. In natural conditions, assessment of visual signals may be affected by turbidity fluctuations. I found that increased turbidity affected contest winner, and transmission or perception of visual stimuli. Together, these studies provide a better understanding of stomatopod communication, and, more broadly, help us to understand the evolution of color signals across organisms and visual systems.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Biology.; Advisor: Sara Lewis.; Committee: Randi Rotjan, Jan Pechenik, Elizabeth Crone, Phil Starks, and Tamra Mendelson.; Keywords: Biology, Ecology, and Behavioral sciences.